2018 AIAA/CEAS Aeroacoustics Conference 2018
DOI: 10.2514/6.2018-2964
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of the Flow Permeability of Metal Foams on Trailing Edge Noise Reduction

Abstract: The turbulent flow over a NACA 0018 airfoil with porous trailing edge inserts and the resulting scattered turbulent-boundary-layer trailing edge noise are studied to investigate the effect of the cross-flow through the material. The experiments are performed at a chord-based Reynolds number of 2.63×10 5 and an angle of attack of 0 •. Two different porous inserts, covering 20% of the chord, are manufactured with the same metal foam (cell diameter of 800 µm and permeability of 27×10 −10 m 2). In order to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 49 publications
(57 reference statements)
7
59
0
Order By: Relevance
“…Above the cross-over frequency, MF inserts generate higher noise than the baseline case, with larger increase being measured for the MF with higher d c . This contribution is generally attributed to the roughness of the material [20,41,42]. For the perforated trailing edges, similar features are reported: with the exception of the frequency band with f c = 630 Hz -where the l h = 1.5 mm insert generates a tonal noise-higher permeability produces larger maximum noise attenuation levels (5 and 9.5 dB for perforated inserts with l h = 3 and 1.5 mm respectively).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Above the cross-over frequency, MF inserts generate higher noise than the baseline case, with larger increase being measured for the MF with higher d c . This contribution is generally attributed to the roughness of the material [20,41,42]. For the perforated trailing edges, similar features are reported: with the exception of the frequency band with f c = 630 Hz -where the l h = 1.5 mm insert generates a tonal noise-higher permeability produces larger maximum noise attenuation levels (5 and 9.5 dB for perforated inserts with l h = 3 and 1.5 mm respectively).…”
Section: Resultssupporting
confidence: 66%
“…These two parameters are obtained by least-squares fitting of Eq. (1) to 20 pressure drop data, measured for Darcian velocities ranging between 0 and 1.1 m/s [19,30]. The porosity σ of the perforated inserts, defined as the ratio of empty-to-solid volume, is also computed as σ = πd 2 h /(2l 2 h ).…”
Section: Fig 3 Sketch Of the Hole Pattern For Perforated Insertsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Equation (1) it follows that the seepage velocity which can be expected for the permeable materials used in this study is low enough to neglect the inertia term. In a previous campaign [16], the physical properties of the metal foam were specified as given in Table 1. Table 1.…”
Section: Flow Resistivitymentioning
confidence: 99%
“…They proposed air flow resistivity as a key parameter to control the low-frequency noise attenuation. More recently, Rubio Carpio et al [16] used permeable metallic foams to replace the rigid trailing edge of a NACA0018 airfoil which led to far-field noise reduction of up to 11 dB. Comparison with porous but non-permeable inserts showed that no noise reduction is achieved when flow communication is neglected.…”
Section: Introductionmentioning
confidence: 99%